Pediatric and adolescent injury in skiing - Provance, A. J.; Daoud, A. K.; Tagawa, A.; Rhodes, J. (Research in Sports Medicine, 2018)
This review examines risks that accompany child and adolescent participation in downhill skiing. Falls and non-collision events were the most common mechanism of injury, but significant data implicate head injuries, blunt abdominal trauma, and spinal trauma as the leading causes of morbidity and mortality in this population. School-aged children and youth (7-14 years) are more likely to sustain an injury, compared to children (0-6 years) and older teenagers (15-17 years). Knee injuries were the most common injury, reported as 10.3%-47.7% of all lower limb injuries. The literature supports helmet use as protective against injury with a reduced risk of head, neck, or face injury in children under 13 years. Future studies are necessary to evaluate injury and risks in the backcountry given the rapid increase of adolescents traveling outside ski areas. Research examining risk factors and preventive measures in youth skiing is also warranted.